Incesto fraterno: raízes arcaicas de seu aparecimento na infância e adolescência - Cynthia da Conceicao Tannure (2018)
Since Freuds studies, the theme of incest has become of the utmost relevance for the psychoanalytic investigation. In view of its problematization, a series of questions has aroused about the genesis of its prohibition and the family and personal conditions that lead to the emergence and perpetuation of incestuous practices. In this way, the starting point of the present study was our clinic experience at CAVAS/UFMG (Research and extension project with children and adolescents victims of sexual abuse) through which we had access to some intriguing cases of fraternal incest, in a family environment of precarious parental care, violence and, sometimes, incest. We started from the hypothesis that such precarious parental care, when internalized, determined the way those children channeled their pulsional demands and desires before the requests of their psychic reality. Therefore, we chose to investigate the archaic roots of the possible existing reasons between the primary investments that failed to contain and appease the excitement and the fraternal bond chosen as a viable destination for such purposes. Following the path of the psychoanalytic research that involves constant reflection between the established theory and the challenges placed by the clinic observations of the psychic movements in a given cultural context - we started our study bringing together Freudian ideas about organization and interdiction of incestuous desires, from the Oedipus and the castration complexes ,and the peculiarities of the fraternal relations, and the history of seduction experienced in in childhood among siblings of close ages. This way, we prioritized the psychoanalyst perspective, which studies and understands the psychic functioning through the internalization of the childrens relations with their objects, in interaction with their defenses and pulsions. Thus, we used the contributions of authors like Melanie Klein, René Kaës, Luís Hornstein and Rosa Jaitin that help understand fraternal incest from the archaic aspects of the relation with the mother and the impossibility of separating from her. From the relation between that unsatisfactory bond, that doesnt create the internal resources to contain and appease excitations, and the lack of obstacles that prevent the renunciation of family objects, come the primitive needs that are renewed in the relations between siblings. This way, the incest, in connection to the functioning of the archaic fraternal complex, will be dominated by a feeling of envy and the narcissistic needs. We tried to interweave these ideas with the constant occurrence of incestuous actions, when one of the siblings is at the beginning of adolescence time when the internalizations, resulting from the relations of the early years, are rearranged.